2016
DOI: 10.1007/s00122-016-2733-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection for wheat traits and trait stability

Abstract: Based on the estimates of accuracy, genomic selection would be useful for selecting for improved trait values and trait stability for agronomic and quality traits in wheat. Trait values and trait stability estimated by two methods were generally independent indicating a breeder could select for both simultaneously. Genomic selection (GS) is a new marker-assisted selection tool for breeders to achieve higher genetic gain faster and cheaper. Breeders face challenges posed by genotype by environment interaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 77 publications
13
69
0
Order By: Relevance
“…Further detailed simulations are possible to consider all existing marker prediction models, the related parameters associated with QTL genetic model, marker distribution and informativeness, training set and test environment (Heffner et al, 2009, 2010; Zhong et al, 2009; Hickey et al, 2014). However, our simulation results are consistent with several empirical reports from GS analyses that prediction accuracies were higher using only the QTL-linked markers or a subset of informative markers (e.g., Spindel et al, 2015; Thavamanikumar et al, 2015; Arruda et al, 2016; Edwards et al, 2016; Huang et al, 2016; Liu et al, 2016). Thus, the simulations in Angus cattle and soybean, along those empirical reports, provided support for our theoretical reasoning to search for more informative FAST SNP markers through RNA-Seq to improve trait prediction accuracy.…”
Section: Theoretical Reasoning and Computer Simulationsupporting
confidence: 91%
“…Further detailed simulations are possible to consider all existing marker prediction models, the related parameters associated with QTL genetic model, marker distribution and informativeness, training set and test environment (Heffner et al, 2009, 2010; Zhong et al, 2009; Hickey et al, 2014). However, our simulation results are consistent with several empirical reports from GS analyses that prediction accuracies were higher using only the QTL-linked markers or a subset of informative markers (e.g., Spindel et al, 2015; Thavamanikumar et al, 2015; Arruda et al, 2016; Edwards et al, 2016; Huang et al, 2016; Liu et al, 2016). Thus, the simulations in Angus cattle and soybean, along those empirical reports, provided support for our theoretical reasoning to search for more informative FAST SNP markers through RNA-Seq to improve trait prediction accuracy.…”
Section: Theoretical Reasoning and Computer Simulationsupporting
confidence: 91%
“…The phenotypes showed reasonably high heritability, as indicated in a prior genomic selection contribution by Huang et al (2016Huang et al ( , 2018 (Table 1). The phenotypes showed reasonably high heritability, as indicated in a prior genomic selection contribution by Huang et al (2016Huang et al ( , 2018 (Table 1).…”
Section: Resultsmentioning
confidence: 80%
“…The same germplasm was used by Huang et al (2016) to study genomic selection for trait stability. The panel was composed of lines from nine breeding programs serving nine states: Indiana, Michigan, Ohio, Missouri, Virginia, Kentucky, Maryland, Illinois, and New York.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies concluded that genomic prediction for yield stability in rye 9 and wheat 10 could be effective. However, to fully exploit plasticity it is important to understand its genetic architecture.…”
mentioning
confidence: 99%